Prevalence of mild cognitive problems in Flemish Nursing homes. (30th September 2020) - De Vriendt, P; Gorus, E; Bilsen, J
Abstract: Background: Mild cognitive decline in Nursing Home (NH) residents without dementia is often noted very late since cognitive demands are relatively low in this setting. Therefore, subtle cognitive changes could remain undetected. This study aimed to evaluate the prevalence of mild cognitive problems in NHs. Methods: First, a file study was performed to exclude residents with a diagnosis of dementia or known cognitive problems (Mini Mental State Examination-MMSE < 24) in 16 NHs. Second, remaining residents were screened for cognition with the Montreal Cognitive Assessment (MoCA). Also, an evaluation of functionality (ADL-Questionnaire), mood (Geriatric Depression Scale), neuropsychiatric symptoms (Neuropsychiatric Inventory Questionnaire) and subjective memory complaints (Informant Questionnaire on Cognitive Decline) was performed. Results: On a total of 1339 residents, 229 persons (17.1%) had no diagnosis of dementia and an MMSE >23. Based on MoCA-cut-offs 2.7% (n = 36), 11.4% (n = 152) and 3.1% (n = 41) could be labelled as cognitively normal (>25), mild cognitive impairment (>16 and <26) and mild dementia (<17) respectively. This resulted in a prevalence of undetected mild cognitive problems of 14.5% (n = 193) in the total NH population. Significant differences between the 3 groups were found for functionality, mood, neuropsychiatric symptoms and subjective memory complaints (all p < 0.05). Conclusions: Considering their advanced age NH residents are vulnerable to develop dementia. This study showed that an important part of them has unnoticed mild cognitive problems. NHs should be aware of this risk group in order to provide adequate prevention and support.